Characterization of antimicrobial peptide activity by electrochemical impedance spectroscopy - Chang, William K. (2008)
Electrochemical impedance spectroscopy performed on surface-supported bilayer membranes allows for the monitoring of changes in membrane properties, such as thickness, ion permeability, and homogeneity, after exposure to antimicrobial peptides (AMPs). We show that two model cationic peptides, very similar in sequence but different in activity, induce dramatically different changes in membrane properties as probed by impedance spectroscopy. Moreover, the impedance results excluded the “barrel-stave” and the “toroidal pore” models of AMP mode of action, and are more consistent with the “carpet” and the “detergent” models. The impedance data provide important new insights about the kinetics and the scale of the peptide action which currently are not addressed by the “carpet” and the “detergent” models. The method presented not only provides additional information about the mode of action of a particular AMP, but offers a means of characterizing AMP activity in reproducible, well-defined quantitative terms.